Effect of CR and FT-paraffin versus SBS modification in terms of conventional and rheological properties - Kok, Baha Vural; Yilmaz, Mehmet; Akpolat, Mustafa (Taylor & Francis Ltd, 2017)
In this study, the rheological and conventional properties of binders prepared with crumb rubber (CR) and FT-paraffin were compared to styrene-butadiene-styrene (SBS)-modified binders' properties. The objective of this study was to determine which modified binders in different combinations of the CR and the FT-paraffin exhibited better performance than the SBS-modified binders, in terms of conventional and rheological properties. Results showed that the additives exhibited different performances for different types of tests. Many of the combinations including the common usage of the CR and the FT-paraffin performed better at high temperature than the SBS modification. Overall, the test results show that the binders prepared by 6% CR with 3 and 4% FT-paraffin and those prepared with 8% CR with 3% FT-paraffin were better binders than the 4% SBS-modified binder, in terms of low and high temperature properties.
Keywords: Crumb rubber; FT-paraffin; SBS; conventional properties; rheological properties